Familiarity increases aggressiveness among clonal fish. (February 2019) - Doran, Carolina; Bierbach, David; Laskowski, Kate L.
Abstract : Understanding how animal groups form and function is a major goal in behavioural ecology. Both genetic relatedness and familiarity among group mates have been shown to be key mediators of group composition. However, disentangling the two in most species is challenging as the most familiar individuals are often the most related, and vice versa. The relatedness between individuals is constant, whereas familiarity is not, and so familiarity may be more likely to mediate interactions in dynamic environments. Here, we manipulated the level of familiarity among groups of the naturally clonal, and genetically identical, Amazon molly, Poecilia formosa, and monitored group behaviour in an open-field assay and when given the opportunity to forage. Contrary to our predictions, fish that were the most familiar with each other showed the highest levels of aggression. Additionally, fish that were less familiar with each other exhibited the highest group cohesion and took the longest to begin feeding, compared to the more familiar fish. These results suggest that familiarity may socially buffer individuals from the perception of risk in novel environments, such as is common in most behavioural assays designed to test group behaviour. Increases in aggression that are associated with increasing familiarity as shown here might be a mechanism by which fish maintain a fission–fusion society with important consequences for the patterns of associations in group-living animals. Highlights: Genetic relatedness and familiarity influence associations among individuals. We disentangled familiarity and relatedness using a clonal fish. Aggression increases and group cohesion decreases with increasing familiarity. In low-familiarity groups there is more egalitarian food sharing. High aggression may provide a selective pressure for a fission-fusion way of life.